Intra-breath-hold residual motion of image-guided DIBH liver-SBRT: an estimation by ultrasound-based monitoring correlated with diaphragm position in CBCT - Vogel, Lena; Sihono, Dwi Seno Kuncoro; Weiß, Christel; Stieler, Florian; Wertz, Hansjörg; Swietochowski, Sandra von; Simeonova-Chergou, Anna; Wenz, Frederik; Blessing, Manuel; Boda-Heggemann, Judit (Radiotherapy and oncology, 2018)
Background and purpose: Craniocaudal motion during image-guided abdominal SBRT can be reduced by computer-controlled deep-inspiratory-breath-hold (DIBH). However, a residual motion can occur in the DIBH-phases which can only be detected with intrafractional real-time-monitoring. We assessed the intra-breath-hold residual motion of DIBH and compared residual motion of target structures during DIBH detected by ultrasound (US). US data were compared with residual motion of the diaphragm-dome (DD) detected in the DIBH-CBCT-projections. Patients and methods: US-based monitoring was performed with an experimental US-system simultaneously to DIBH-CBCT acquisition. A total of 706 DIBHs during SBRT-treatments of metastatic lesions (liver, spleen, adrenal) of various primaries were registered in 13 patients. Residual motion of the target structure was documented with US during each DIBH. Motion of the DD was determined by comparison to a reference phantom-scan taking the individual geometrical setting at a given projection angle into account. Residual motion data detected by US were correlated to those of the DD (DIBH-CBCT-projection). Results: US-based monitoring could be performed in all cases and was well tolerated by all patients. Additional time for daily US-based setup required 8±4min. 385 DIBHs of 706 could be analyzed. In 59% of all DIBHs, residual motion was below 2mm. In 36%, residual motion of 2-5mm and in 4% of 5-8mm was observed. Only 1% of all DIBHs and 0.16% of all readings revealed a residual motion of >8mm during DIBH. For DIBHs with a residual motion over 2mm, 137 of 156 CBCT-to-US curves had a parallel residual motion and showed a statistical correlation. Discussion and conclusion: Soft-tissue monitoring with ultrasound is a fast real-time method without additional radiation exposure. Computer-controlled DIBH has a residual motion of <5mm in >95% which is in line with the published intra-breath-hold-precision. Larger intrafractional deviations can be avoided if the beam is stopped at an US-defined threshold.
Gesehen am 26.03.2019